2008
DOI: 10.1088/0031-9155/53/17/022
|View full text |Cite
|
Sign up to set email alerts
|

Breast tumor classification using axial shear strain elastography: a feasibility study

Abstract: Recently, the feasibility of visualizing the characteristics of bonding at an inclusion-background boundary using axial-shear strain elastography was demonstrated. In this paper, we report a feasibility study on the utility of the axial-shear strain elastograms in the classification of in vivo breast tumor as being benign or malignant. The study was performed using data sets obtained from 15 benign and 15 malignant cases that were biopsy proven. A total of three independent observers were trained, and their se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(87 citation statements)
references
References 36 publications
1
85
0
Order By: Relevance
“…Recently, we have demonstrated that axial-shear strain elastography may aid in breast tumor classification by adding independent tissue mechanics information pertaining to the bonding of a tumor to its surrounding (ThitaiKumar et al 2007(ThitaiKumar et al , 2008. The underlying hypothesis for the previously reported work was based on the characteristic differences in the mobility of benign and malignant lesions noted in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that axial-shear strain elastography may aid in breast tumor classification by adding independent tissue mechanics information pertaining to the bonding of a tumor to its surrounding (ThitaiKumar et al 2007(ThitaiKumar et al , 2008. The underlying hypothesis for the previously reported work was based on the characteristic differences in the mobility of benign and malignant lesions noted in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…It can display the texture of the tissue and reflect the biological characteristics of the mass [4]. It shows promising prospects in differentiating benign from malignant breast tumor [5][6][7][8][9][10][11]. The semi-quantitative sonoelastography makes the elasticity evaluation more easily [12].…”
Section: Introductionmentioning
confidence: 99%
“…Although the total number of females referred for interventional diagnostic procedures represents a small percentage of any screened population, the healthcare resources consumed by such females are disproportionately high (11). Further, the pathological result is benign in up to 75% of all cases (11)(12)(13). Therefore, a reliable, noninvasive, costeffective method helping to differentiate benign from malignant breast lesions, thus reducing the number of unnecessary interventional diagnostic procedures, would be valuable.…”
mentioning
confidence: 99%